Uncommon Coronary Abnormalities in a Patient with Discoid Lupus Erythematosus - Valencia, Damian; Linares, Juan; Das, Sulagna; Valencia, Victor; Yatsynovich, Yan (International Journal of Angiology, 2019)
A 43-year-old male presented with shortness of breath and palpitations. Physical examination was significant for skin lichenification, an erythematous maculopapular rash with annular plaques, a fissured tongue, and digital clubbing. Electrocardiogram captured a supraventricular tachycardia and right bundle branch block. Left heart catheterization found several proximal left coronary artery branch aneurysms, a right coronary–pulmonary artery fistula, venous–luminal vessels between the right heart chambers and cardiac veins, and thebesian venous lakes. Functional cardiac capacity was reduced, with left ventricular ejection fraction of 35 to 40%, on ventriculogram. A diagnosis of discoid lupus erythematosus was established after skin biopsies revealed systemic lupus erythematosus-like features but negative anti-nuclear, anti-Smith, anti-ds-deoxyribonucleic acid, anti-Ro, and anti-La antibodies. The case reported is unique, in that while our patient had pathologic electrophysiologic changes typically seen with autoimmune disease, the patient had many anatomical cardiac anomalies without atherosclerotic coronary disease. It is uncertain whether these findings are purely incidental or are related to an underlying genetic disorder.
Keywords: coronary aneurysm; discoid lupus erythematosus; thebesian venous lakes; fistula; venous–luminal vessels; coronary–pulmonary fistula; coronary steal